A Floruit of Poliorcetics: The Siege of Rhodes, 305/304 BC - Wheatley, Pat (Anabasis. Studia Classica et Orientalia, 2016)
The year-long siege of Rhodes in 305 BC by Demetrius Poliorcetes, during which siege machinery of a phenomenal scale was deployed, was a standout event in the period of the Diadochi, but it has never received a dedicated treatment in English. This essay therefore aims to provide an analytical survey of the campaign, and offers fresh insights into matters of motive, topography, tactics, chronology, and historiography. I also seek to supply a more balanced perspective on the trope of Antigonid ‘failure’ at Rhodes, which has persisted since the time of Plutarch.